VD_FINDINFO HC / 2023 / 674 vom 19. Oktober 2023 - VD Tribunal cantonal (2023)
BAIL À LOYER, EXPULSION DE LOCATAIRE, REJET DE LA DEMANDE, CAS CLAIR, ABUS DE DROIT, FORMULE OFFICIELLE | 257d CO, 270 al. 2 CO, 257 CPC (CH)